2011
DOI: 10.1101/lm.024182.111
|View full text |Cite
|
Sign up to set email alerts
|

Exaggerated NMDA mediated LTD in a mouse model of Down syndrome and pharmacological rescuing by memantine

Abstract: The Ts65Dn mouse is the best-studied animal model for Down syndrome. In the experiments described here, NMDA-mediated or mGluR-mediated LTD was induced in the CA1 region of hippocampal slices from Ts65Dn and euploid control mice by bath application of 20 mM NMDA for 3 min and 50 mM DHPG for 5 min, respectively. We found that Ts65Dn mice display exaggerated NMDA-induced, but not mGluR-induced, LTD in the CA1 region of the hippocampus compared with euploid control animals. In addition, this abnormal level of LTD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 38 publications
(35 reference statements)
0
37
2
Order By: Relevance
“…This latter effect can be reversed with the uncompetitive NMDA receptor antagonist memantine [78] and also improves the cognitive performance of Ts65Dn mice [7981]. These results draw a clear link between altered synaptic plasticity in the hippocampus and cognitive performance in the Ts65Dn mouse model of Down syndrome.…”
Section: Modeling Ds Cognitive Impairmentmentioning
confidence: 86%
“…This latter effect can be reversed with the uncompetitive NMDA receptor antagonist memantine [78] and also improves the cognitive performance of Ts65Dn mice [7981]. These results draw a clear link between altered synaptic plasticity in the hippocampus and cognitive performance in the Ts65Dn mouse model of Down syndrome.…”
Section: Modeling Ds Cognitive Impairmentmentioning
confidence: 86%
“…Of these models, Ts65Dn is most widely used and consists of a genomic fragment with 49% syntenic regions and 55% of the HSA21 gene orthologs triplicated [50, 51]. These mice have lower dendritic density, enlarged spine heads, as well as impaired hippocampal-dependent learning and memory, tested using the Morris water maze, as well as impaired LTP at excitatory hippocampal synapses [5255], yet enhanced LTD [56, 57]. Ongoing research in DS has focused on creating mouse models with smaller selections of trisomic genes included in the DS critical region.…”
Section: Spine Dysgenesis In Autism Related Disordersmentioning
confidence: 99%
“…In fact, some studies have attempted to reverse the cognitive impairments observed in Ts65Dn mice by using GABAA [28] or GABAB [27] receptor antagonists, obtaining promising results. Another way to act over the system was blocking NMDA receptors using memantine, reflecting that the problem is more complex that just over-inhibition [29].…”
Section: Introductionmentioning
confidence: 99%